Epidemiology, Diagnosis, and Antimicrobial Treatment of Acute Bacterial Meningitis - Brouwer, Matthijs C. (American Society for Microbiology (ASM), 2010)
Summary: The epidemiology of bacterial meningitis has changed as a result of the widespread use of conjugate vaccines and preventive antimicrobial treatment of pregnant women. Given the significant morbidity and mortality associated with bacterial meningitis, accurate information is necessary regarding the important etiological agents and populations at risk to ascertain public health measures and ensure appropriate management. In this review, we describe the changing epidemiology of bacterial meningitis in the United States and throughout the world by reviewing the global changes in etiological agents followed by specific microorganism data on the impact of the development and widespread use of conjugate vaccines. We provide recommendations for empirical antimicrobial and adjunctive treatments for clinical subgroups and review available laboratory methods in making the etiological diagnosis of bacterial meningitis. Finally, we summarize risk factors, clinical features, and microbiological diagnostics for the specific bacteria causing this disease.